Making Christianity Safe for Democracy: I. The Moral Meaning of Democracy - Smith, Gerald Birney (The biblical world, 1919)
This is the first of six articles by Professor Smith. As the striking title indicates, they will treat of Christianity not as a theoretical system but as a modern democratic movement. In a day when we are apt to lose ourselves in the dust storms of rhetoric and think we have reached reality when we have acquired a vocabulary, these articles put the issue frankly but with the authority of reality. It is easy for the church to mistake complacency for faith and the avoidance of deficits for providential guidance. But the next few years will be times that try men's souls. Only a religion full of faith in God and fraternal service of mankind will be anything more than a social parasite.